Postpartum Depression and Its Contributing Factors among Mothers during the COVID-19 Pandemic in North Jakarta, Indonesia - Venna Yaasmiin Aadillah; Irma Nurbaeti (Nurse Media: Journal of Nursing, 2023)
Background: Postpartum depression is a common psychological problem that occurs after birth. It has become especially prevalent in the era of the COVID-19 pandemic. Several factors contribute to postpartum depression. However, a limited study evaluated factors contributing postpartum depression among mothers during the COVID-19 pandemic, particularly in Indonesia.